2017
DOI: 10.1128/jcm.00987-17
|View full text |Cite
|
Sign up to set email alerts
|

Variable Sensitivity in Molecular Detection of Zika Virus in European Expert Laboratories: External Quality Assessment, November 2016

Abstract: Zika virus (ZIKV) infections are a significant public health concern. A strong capability for ZIKV detection is an absolute requirement for adequate preparedness and response strategies and individual patient care. The objective of this study was to assess and improve the capability of European expert laboratories for molecular testing for ZIKV through an external quality assessment (EQA) scheme. Laboratories were provided a panel of 12 samples which included negative samples, samples containing African-or Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…To properly assess the actual capability of the laboratories to detect (sub)clinical 2019-nCoV cases and to provide directions for corrective actions, proficiency testing by external quality assessment (EQA) is essential and urgently needed. The importance of EQA was illustrated in the European ZIKV response where timely implementation was not matched by an overall good capability [17]. Forty of the 47 responding laboratories in this study indicated that they will participate in such an assessment.…”
Section: Discussionmentioning
confidence: 84%
“…To properly assess the actual capability of the laboratories to detect (sub)clinical 2019-nCoV cases and to provide directions for corrective actions, proficiency testing by external quality assessment (EQA) is essential and urgently needed. The importance of EQA was illustrated in the European ZIKV response where timely implementation was not matched by an overall good capability [17]. Forty of the 47 responding laboratories in this study indicated that they will participate in such an assessment.…”
Section: Discussionmentioning
confidence: 84%
“…EVD-LabNet represents a laboratory and knowledge platform for support of clinical and public health preparedness and response through laboratory capacity and capability building. Moreover it provides access for ECDC, national public health authorities and its member laboratories to reference diagnostics, expertise and knowledge exchange [20,21]. EVD-LabNet comprises 61 expert laboratories in 30 European Union and European Economic Area (EU/EEA) countries, seven laboratories in seven EU pre-accession countries, three in two other European countries and six in six non-European countries.…”
Section: Emerging Viral Diseases-expert Laboratory Networkmentioning
confidence: 99%
“…2 Furthermore, in 2016, for the first time in documented history, confirmed yellow fever virus was exported in travellers from Africa to Asia, where about 2 billion immunologically naive people live in areas inhabited by the Aedes aegypti mosquito vector and are at risk for transmission. 3 The casefatality rate of yellow fever is among the highest of all arboviral diseases, underscoring the threat of a newly emerging epidemic disease problem in Asia.…”
Section: An Update On the Severe Outbreak Of Hiv In Kot Imrana Pakistanmentioning
confidence: 99%
“…Albeit to a lesser extent, similar problems were also observed in European laboratories, for which the overall risk of false-negative results was 14•5% (8•9-20•1) and the overall risk of false-positive results was 4•4% (2•1-6•8). 3 The similarities between the studies from Brazil and Europe show that adequate laboratory diagnosis of Zika virus infection is universally challenging. Unreliable Zika virus diagnostics have a huge effect on individual and public health, potentially including illegal abortions based on false-positive test results, 4 unwarranted delays of pregnancy, and biased estimates of the absolute risk of congenital disease upon maternal infection during pregnancy.…”
mentioning
confidence: 99%